2018
DOI: 10.3390/f9110690
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Chemical Responses of Eastern White Pine (Pinus strobus L.) to Blue-Stain (Ophiostoma minus) Inoculation

Abstract: The increases in temperature have recently allowed the southern pine beetle (Dendroctonus frontalis Zimm.; SPB) and its associated fungi to expand its natural range to northern pine forests. In this study, vigorous eastern white pine mature trees were used to evaluate constitutive and induced response to the southern pine beetle, using O. minus as a proxy. We evaluated histological and chemical changes in P. strobus in response to the fungus at 28and 65-days post inoculation (dpi). Inoculation with O. minus re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Whether or not fire proves to be a long-term solution to southern pine beetle persistence (Lesk et al, 2017), it would be very useful to identify whether forest or prescribed fire play a decisive role in slowing acceleration of blue stain fungi aggregation (Ophiostoma minus) associated with southern pine beetle (Arango-Velez et al, 2018). Following such a study, if results warranted, an analysis of anthropogenic PyC inputs might also be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not fire proves to be a long-term solution to southern pine beetle persistence (Lesk et al, 2017), it would be very useful to identify whether forest or prescribed fire play a decisive role in slowing acceleration of blue stain fungi aggregation (Ophiostoma minus) associated with southern pine beetle (Arango-Velez et al, 2018). Following such a study, if results warranted, an analysis of anthropogenic PyC inputs might also be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activation, synthesis and accumulation of combined constitutive and induced SMs may be too slow to reach effective levels against mass‐attacking beetles and prevent lethal damage, when populations are high (Boone et al ., ). In addition, field studies have shown that local NSC storage was used for production of induced SMs in response to simulated or actual bark beetle attack (Raffa et al ., ; Roth et al ., ) or fungal infection (Goodsman et al ., ; Arango‐Velez et al ., ), while NSC stored in distant organs could not be mobilized to attacked stem sections (Wiley et al ., ). Such results indicate that mobilization and transport of NSC play an important role in allocation to induced defence in conifers.…”
Section: Carbon Allocation To Tree Sm Biosynthesismentioning
confidence: 99%
“…In several plant species, catechins have been found to provide protection against, for example, oxidative stress, herbivore attacks, and bacterial invasions. In conifers, catechin production is induced in response to inoculation with E. polonica [27][28][29], ophiostomatoid fungi [28,30], and other fungal pathogens [31]. Within the last decade, new light has been shed on catechin biosynthesis and functions as defensive compounds in Norway spruce [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%